ELETROESTIMULAÇÃO PARA OS MEMBROS INFERIORES EM CRIANÇAS E ADOLESCENTES COM PARALISIA CEREBRAL: UMA REVISÃO DE LITERATURA (Movimenta (ISSN 1984-4298), 2024)
BACKGROUND: The use of neuromuscular electrical stimulation (NMES) and/or functional electrical stimulation (FES) combined with functional activities can result in better functional mobility in children and adolescents with Cerebral Palsy (CP). OBJECTIVE: The objective of this study was to review the literature on the use of electrical stimulation on the lower extremities of children and adolescents with CP. METHODS: Literature review including clinical trials published between January 2018 and December 2023 was performed, with participants with CP aged between 0 (zero) and 18 (eighteen) years. The studies’ titles and abstracts were evaluated, to later be read in full. Systematic review and studies that did not have this intervention were excluded. To evaluate the methodological quality of the selected clinical trials, the PEDro Scale was used. RESULTS: Seven studies with moderate methodological quality were included (PEDro=6.75; between 4-8). The use of NMES or FES combined with exercise in children and adolescents with CP resulted in reduced spasticity, improved muscular physiology and improved gait patterns and mobility in individuals with CP, presenting statistically significant results in GMFM (p